2012
DOI: 10.1515/hf-2012-0126
|View full text |Cite
|
Sign up to set email alerts
|

Inverse gas chromatography and XPS of extracted kraft pulps

Abstract: Aguarda recepção da versão digital do autor ou a digitalização da versão impressa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Considering the changes in the surface properties determined by IGC, NaIO 4 was found to be a weaker oxidizing agent. The value of the parameter measured for kraft lignin (35.2 mJ/m 2 ) is in agreement with the values reported in the literature [ 62 ]: from 30 to 39 mJ/m 2 at 40 °C depending on the kraft pulp. Belgacem et al reported slightly higher values of for kraft lignin (46 mJ/m 2 ) but that material came from a different source than that used in the present study [ 63 ].…”
Section: Resultssupporting
confidence: 91%
“…Considering the changes in the surface properties determined by IGC, NaIO 4 was found to be a weaker oxidizing agent. The value of the parameter measured for kraft lignin (35.2 mJ/m 2 ) is in agreement with the values reported in the literature [ 62 ]: from 30 to 39 mJ/m 2 at 40 °C depending on the kraft pulp. Belgacem et al reported slightly higher values of for kraft lignin (46 mJ/m 2 ) but that material came from a different source than that used in the present study [ 63 ].…”
Section: Resultssupporting
confidence: 91%
“…The effect of preliminary hot water extraction on the surface properties of eucalypt and sugar maple (Acer Saccharum) kraft pulps was also considered: kraft pulps with kappa number of 15 obtained from Acer saccharum and Eucalyptus globulus prepared with and without hot water extraction (HWE) before cooking were analysed by IGC and XPS (Duarte et al 2012;Gamelas et al 2013). It should be noted that HWE is used to extract hemicelluloses from the material (the xylan amount is reduced from about 16 % in the reference pulp to ca.…”
Section: Cellulose Analyses By Igcmentioning
confidence: 99%
“…Cellulose and lignocellulosic materials belong to a class of materials that has been thoroughly studied using IGC, because of the importance of their physicochemical surface properties in the context of papermaking, textile area and, particularly, in the production of composites with polymeric matrices (Felix et al 1993;Chtourou et al 1997;Gauthier et al 1998a;Matuana et al 1998;Gulati and Sain 2006a;Gulati and Sain 2006b;Tze et al 2006a, b;Dominkovics et al 2007;Wang and Sain 2007;Gregorova et al 2009;Rocha et al 2009;Tonoli et al 2010;Gamelas et al 2012Gamelas et al , 2013. The purpose of this article is to critically review and discuss the most relevant results available in the literature about the use of IGC to characterize the surface of cellulosics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lowest median value of γ sp of F1-PCL among all lignin -g- PCLs (Table ) means the strongest polar–polar affinity . Additionally, a higher hydrophilicity index, defined as the ratio of γ sp /(γ sp + γ d ), of KL-PCL than that of KL but lower than that of PCL (Table ) indicates that lignin incorporation can intensify the hydrophobicity of PCL, which might be because lignin introduced aromatic groups to long-chain PCL esters. , The lowest hydrophilicity index of F1-PCL (Table ) may be ascribed to the highest content of hydrophobic groups like ester and alkyl groups because of the longest PCL chains. However, although F2-PCL has a longer PCL chain length (more ester and alkyl groups) than F3-PCL, it still exhibits a higher hydrophilicity index (0.24 vs 0.19).…”
Section: Resultsmentioning
confidence: 99%